ISOLATION AND STRUCTURE ELUCIDATION OF THE CUSHION PLANT POTENTILLA ARTICULATA - Muhammad Hanafi; Shibata Kozo; Mamoru Kanzaki (Research Center for Chemistry - LIPI, 1996)
Methanol extract of the whole plant of P. articulata Franch was fractionated by using open column silica gel chromatography following identification, resulted in the isolation of known phytoceramides, N-(2'-hydroxy-acyl)-2-amino1,3,4trihydroxy-8-octadecene) (1), which also isolated from Urtioca dioca and Thylacospermum caespitosum, and two known steroids, identified as -sitosterol (2), 3B-O-B-D-glucopyranosylsitosterol (3), which have also been isolated from Prunella vulgaris L. var. Iilacina (Labiatae). Triterpenoic acids were elucidated as 2B,19a-dihydroxyursolic acid (4), a mixture of Zcc-monohydroxyursclic acid (5) and 2a-monohydroxyoleanolic acid (6), also found in Geurn japonicum Thunberg, 19a-monohydro-xyursolic acid (7), a mixture ursolic acid (8) and oleanolic acid (9), which were also obtained in Isodon japonicus Hara. Their structure identifi-cations were based on chemical and spectroscopic methods.